Moroccan Arabic or Algerian Arabic? The study of the Moroccan Arabic in Spain during the 19th. The book of Pedro María del Castillo y Olivas - Moscoso García, Francisco (Anaquel de Estudios Árabes, 2011)
The book Diálogos españoles-árabes ó guía de la conversación mogharbi (Spanish-Arabic Dialogs or Moroccan Conversation Guide) was written in 1860 by Pedro María del Castillo y Olivas. Its study reflects that the Arabic used was Algerian and a plagiarism of the book Guide written by Delaporte, in spite of its aim to be addressed to the Spanish Military that occupied Tetouan after the Spanish- Moroccan war. Its Edition is also a reflect of the Africanism Spirit that Spain lived during the 19th.